"Make-or-buy" of peripheral services in manufacturing: Evidence from Spanish plant-level data - Alberto Bayo-Moriones; José Enrique Galdón-Sánchez; Ricard Gil (Institute for the Study of Labor (IZA), 2013)
In this paper we empirically explore the make-or-buy decisions of peripheral services in manufacturing plants using detailed information on a data set from a new plant-level survey from 926 plants distributed in all manufacturing industries in Spain. In particular, survey respondents are asked how their contracting practices of peripheral services had changed in the last three years. The answer to this question is informative of the changes in the importance of backward integration for each of the plants interviewed. Using other information provided in the survey, we relate reported changes in backward integration to changes in other relevant plant characteristics. We show that increases in outsourcing of services are positively correlated with increases in the plant's market share as well as increases in product market competition and product prices. These findings are robust to controlling for whether plants belong to single-plant or multi-plant firms. This result is consistent with the view that market size limits the degree of specialization at the plant level in the Spanish manufacturing industry.
Keywords: L23; L22; L60; 330; make-or-buy; peripheral services; manufacturing; market share; competition; Verarbeitendes Gewerbe; Make or Buy; Outsourcing; Unternehmensdienstleistung; Marktanteil; Wettbewerb; Spanien